Beyond Tropical Storms: Understanding Disturbance and Forest Dynamics - Heartsill-Scalley, Tamara; López-Marrero, Tania (Frontiers in Forests and Global Change, 2021)
Most of the knowledge of tropical storm effects on forests is from studies conducted in reserves and protected areas. Effects on other settings such as urban forests, coastal forests, and in landscapes with mixed land uses and covers are, comparatively, less studied. Yet research from a range of forest types and landscape compositions is needed to inform actions associated with management, mitigation, or restoration efforts before and after storms. Studies of forests comprising various conditions, along with long-term observations, would offer unique insights into the varied and cumulative effects of tropical storms on forest ecosystems. The Caribbean island of Puerto Rico is one of the sites where most tropical storm-forest studies are conducted, yet studies come from a limited set of sites. Using Puerto Rico as a case study, we emphasize the need for broader research approaches that represent the wider range of forests that are exposed to tropical storms. Such an approach will provide valuable knowledge and understanding needed to inform and take actions across landscape settings, forest context, and socio-environmental conditions.